EU civil justice: current issues and future outlook - Hess, Burkhard; Bergström, Maria; Storskrubb, Eva (Swedish studies in European law, 2016)
The state of the civil justice union / Burkhard Hess -- Lis pendens and jurisdiction clauses : open issues / Gilles Cuniberti -- ADR/ODR : too much optimism in the promotion of cross-border trade? / Jim Davies -- Top-level domains and ADR : what protection of consumer interests under ICANN's new gTLD program? / Cristina M Mariottini -- "Trusted with a muzzle and enfranchised with a clog" : the British approach to European civil procedure / Carla Crifò -- European procedures on debt collection : nothing or noting? : experiences and future prospects / Xandra E Kramer -- The small claims regulation : on the way to an improved european procedure / Cristian Oro Martinez -- The Nordic input on the EU's cooperation in family and succession law : exporting union law through "Nordic exceptions" / Maarit Jänterä-Jareborg -- The European certificate of succession : portrait of a new instrument in European private international law / Björn Laukemann -- "Opt-in is out and opt-out is in" : dimensions based on Nordic options and the commission's recommendation / Laura Ervo -- The crux of the matter : funding and financing collective redress mechanisms / Stefaan Voet -- Legal standing in collective redress actions for breach of EU rights : facilitating or frustrating common standards and access to justice? / Rebecca Money-Kyrle -- Abolition of exequatur, all in the name of mutual trust! / Marie Linton -- On the abolition of exequatur / Marta Requejo Isidro -- Mutual recognition as a governance strategy for civil justice / Eva Storskrubb -- Mutual recognition in civil and criminal justice : towards order and method / Maria Bergström
Includes papers presented at the conference "Civil Justice in the EU: Growing and Teething" held in 2013 in Uppsala organised by the Swedish Network for European Legal Studies (SNELS) in collaboration with the Max Planck Institute in Luxembourg for International, European and Regulatory Procedural Law, and Uppsala University.-- ECIP preface
Keywords: Aufsatzsammlung; Konferenzschrift; Privatrecht; Gerichtsbarkeit; Zivilprozess; Europäische Union